Impacted iron nail in the orbit and maxillary sinus through a corneo-scleral perforation: a case report - Kharel Sitaula, Ranju; Gautam, V; KC, Krishna; Shah, DN (Nepalese Journal of Ophthalmology, 2013)
Introduction: Open globe injury is one of the commonest ophthalmic emergencies, and when accompanied by intraocular foreign bodies, the condition carries a poorer prognosis. Objective: To report a rare case of perforating injury of the globe with an iron nail which got lodged in the maxillary sinus. Case: A ten-year-old boy presented with the history of sudden painful loss of vision in his right eye. He reported that he was hit forcefully by the tail of a cow a day before the presentation. There was no perception of light in that eye. The ocular examination revealed a full thickness corneo-scleral perforation with prolapsed uveal tissue. The X-ray of the right orbit showed an impacted foreign body in the inferior orbit and computed tomography scan of the orbit confirmed the presence of a vertically impacted metal piece in the right orbit and right maxillary sinus. The repair of the perforation and removal of the impacted nail was done in two stages. The globe anatomy was maintained but the vision could not be restored due to the grave nature of the trauma. Conclusion: Perforating globe injury is an important cause of monocular blindness. Nepal J Ophthalmol 2013; 5(10): 268-271 DOI: http://dx.doi.org/10.3126/nepjoph.v5i2.8742